PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA KEDAI WELCOME GINGER DI JAKARTA - Casmudi Casmudi; Yayak Heriyanto (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The intended observation has the aim of being able to see the impact of the quality of service on customer satisfaction at the Welcome Ginger Shop in Jakarta. The method used in this research is quantitative. Data collection techniques were used in the form of questionnaires and literature. The population of this research is the customer of People at the Welcome Ginger shop in Jakarta. The method of obtaining samples in this study is the non-probability of taking several objects by means of population sampling. Objects as many as 69 samples. The study of the data used was a multiple linear regression study using the help of IBM Statistics software version 26. The study shows that the quality of goods/products has an effect on customer satisfaction of 46.97%. Service Quality has an impact of 18.52% on Customer Satisfaction. Product Quality and Service Quality have a significant impact on Customer Satisfaction. Product Quality and Service Quality simultaneously affect the Client Satisfaction variable with a value of 65.5% explained for reasons that are not included in this observation